Attenuation of adverse cardiac effects in prednisolone-treated δ-sarcoglycan-deficient mice by mineralocorticoid-receptor-antagonism - Bauer, Ralf; Blain, Alison; Greally, Elizabeth; Lochmüller, Hanns; Bushby, Kate; MacGowan, Guy A.; Straub, Volker (Neuromuscular disorders, 2010)
We have tested the hypothesis that the adverse effects of glucocorticoids in the δ-sarcoglycan-deficient (Sgcd-null) mouse are due to additional mineralocorticoid effects. We investigated the effects of spironolactone, an unselective mineralocorticoid-receptor antagonist, on in vivo cardiac haemodynamics, cardiomyocyte damage and fibrosis in prednisolone treated Sgcd-null mice. Oral spironolactone given to 8-week-old Sgcd-null non-steroid treated mice had beneficial effects on systolic function by improving myocardial contractility when assessed by pressure-volume loops. Given in combination with prednisolone, spironolactone prevented steroid-induced deterioration of cardiac haemodynamics and acute sarcolemmal damage but not cardiac fibrosis. This study demonstrates the beneficial effects of oral spironolactone on cardiac haemodynamics in Sgcd-null mice and its ability to prevent some of the adverse effects of glucocorticoids.